Development of Pictograms to Communicate Technological Solution Instructions (Labeling) Among Low- Literacy Users - Kisaalita, William S.; Sempiira, Edison J. (Ergonomics in Design, 2022)
Conveying information for appropriate use of devices is uniquely challenging in low-resource settings. Drug makers have previously developed culturally meaningful informational pictograms to, for example, convey timing of doses, among low-literacy patients. We tested a similarly structured process among Ugandan smallholder farmers. Over 67% of the pictograms scored a passing grade after the second round of testing, meeting our overall success criterion. The process is efficacious in developing instructional/teaching (labeling) pictograms. These findings can help solution/device developers for low-resource settings to provide correctly interpretable pictograms and thus eliminate misuse-driven low uptake.